Uridine treatment protects against blood–brain barrier disruption in a rat model of Li-pilocarpine-induced status epilepticus - Aydin, Birnur; Ocalan Esmerce, Busra; Cakir, Aysen; Tuncak, Sueda; Koc, Cansu; Cansev, Mehmet; Alkan, Tulin (Frontiers in Neuroscience, 2025)
IntroductionBlood–brain barrier (BBB) disruption is one of the most striking changes triggered by status epilepticus, which deserves specific attention in terms of novel treatment approaches targeting epileptogenesis. Uridine is a pyrimidine nucleoside with neuroprotective, antiepileptic and antiepileptogenic effects; however, its mechanism of action is not fully characterized. In this study, we aimed to investigate the short-term outcomes of uridine treatment on status epilepticus-induced-BBB dysfunction in an animal model.MethodsStatus epilepticus was induced by lithium and pilocarpine administration in male Sprague–Dawley rats which were post-treated with intraperitoneal injection of saline or uridine (500 mg/kg b.w.; twice a day) for 2 days. Blood–brain barrier structural integrity was assessed by measuring expressions of endothelial tight junction proteins zonula occludens-1 (ZO-1) and occludin, matrix metalloproteinases (MMP-2 and MMP-9), aquaporin-4 (AQP4) water channel and its anchoring protein α1-syntrophin in hippocampal tissue 48 h after SE. Additionally, BBB permeability was determined by measuring brain edema and serum S100B levels.ResultsThe data showed that uridine significantly prevented the reduction in ZO-1 and α1-syntrophin protein levels and attenuated serum S100B levels, indicating protective effects on BBB integrity and AQP4 polarization. In contrast, uridine enhanced brain water content in SE-induced rats, a finding that might be a result of maintained AQP4 polarization and enhanced cytotoxic edema.DiscussionTogether, our results showed for the first time that post-seizure treatment with uridine provides protection against BBB disruption in an experimental SE model; nevertheless, the long-term effects of this treatment warrant further investigation.